2020
DOI: 10.1186/s13045-020-00928-9
|View full text |Cite
|
Sign up to set email alerts
|

DT2216—a Bcl-xL-specific degrader is highly active against Bcl-xL-dependent T cell lymphomas

Abstract: Background: Patients with advanced T cell lymphomas (TCLs) have limited therapeutic options and poor outcomes in part because their TCLs evade apoptosis through upregulation of anti-apoptotic Bcl-2 proteins. Subsets of TCL cell lines, patientderived xenografts (PDXs), and primary patient samples depend on Bcl-xL for survival. However, small molecule Bcl-xL inhibitors such as ABT263 have failed during clinical development due to on-target and dose-limiting thrombocytopenia. Methods: We have developed DT2216, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 41 publications
(63 reference statements)
4
72
0
Order By: Relevance
“…Crystal structures of the small molecule bound to VHL provided insight into suitable attachment points to create PROTACs ( 56 ). Indeed, several studies have now shown that this ligand can be incorporated to produce successful PROTACs ( 17 , 24 , 25 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ). In fact, the VHL ligand is one of the most used E3 ligase recruiting elements in the PROTAC field to date.…”
Section: Hijacking Of the Ups: Protacsmentioning
confidence: 99%
“…Crystal structures of the small molecule bound to VHL provided insight into suitable attachment points to create PROTACs ( 56 ). Indeed, several studies have now shown that this ligand can be incorporated to produce successful PROTACs ( 17 , 24 , 25 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ). In fact, the VHL ligand is one of the most used E3 ligase recruiting elements in the PROTAC field to date.…”
Section: Hijacking Of the Ups: Protacsmentioning
confidence: 99%
“…This intervention reduced disease progression and increased survival in a TCL PDX mouse model dependent on both Bcl-2 and Bcl-xl. (He et al, 2020;Zhang et al, 2020). The same PROTAC approach has been used to reduce platelet toxicity of navitoclax, a known Bcl-2 and Bcl-xl dual inhibitor (He et al, 2020).…”
Section: Fsfc Contributions To Cancer Immunotherapy Researchmentioning
confidence: 99%
“…(He et al, 2020;Zhang et al, 2020). The same PROTAC approach has been used to reduce platelet toxicity of navitoclax, a known Bcl-2 and Bcl-xl dual inhibitor (He et al, 2020). In these studies, FSFC was implemented to evaluate T cells, B cells, myeloid cells, hematopoietic progenitors and hematopoietic stem cells in bone marrow.…”
Section: Fsfc Contributions To Cancer Immunotherapy Researchmentioning
confidence: 99%
“…To avoid the on-target toxicity of BCL-X L inhibitors to platelets, we have recently reported the development of the first-in-class BCL-X L degrader—a proteolysis-targeting chimera (PROTAC) referred to as DT2216—targets BCL-X L to the von Hippel-Lindau (VHL) E3 ligase for ubiquitination and subsequent proteasomal degradation 16 . Because platelets express a low level of VHL E3 ligase, DT2216 has minimal effect on platelets but exhibits an improved cytotoxicity against various cancer cells that are dependent on BCL-X L for survival 16 , 17 . We also developed another similar PROTAC PZ15227 that uses cereblon (CRBN) E3 ligase to induce BCL-X L polyubiquitination and degradation 18 .…”
Section: Introductionmentioning
confidence: 99%